[Hart's Cut, Trinidad] - (:unkn) unknown (Wilsons Ltd., [Trinidad and Tobago], 2011)
Hart’s Cut derives it name from Daniel Hart, who in 1856 cut a narrow channel through the neck of Point Gourde to allow small boats to pass from Carenage to Chaguaramas Bay. Hart's Cut existed well into the twentieth century before it was abandoned and filled in.
Colour: Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Straits--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Chaguaramas; Boats and boating--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Hart's Cut (Chaguaramas)